The Comparison of Supervision of Notaries and Land Deed Making Officials - Sulthon Faiz Saifuddin; Ira Alia Maerani (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Notaries and Land Deed Making Officials are public officials who are given the task, obligation and authority to make authentic deeds and are usually held by one person. Supervision of notaries and Land Deed Making Officials is a must because mistakes or omissions often occur during carrying out their positions. The author in this study tries to compare the supervision carried out on the notary and the Land Deed Making Officer with the aim of knowing the advantages and disadvantages of each supervisor based on the theory of supervision. This research is a normative juridical research by examining secondary data which is analyzed deductively. There are two legal theories used in this research, namely the theory of state power and the theory of supervision. The results showed that the supervision of the notary was carried out by two supervisory institutions, namely the Supervisory Council and the Honorary Council, while the supervision of the Land Deed Making Officer was carried out by two institutions, namely, the Supervisory Council and the Supervisor of the Land Deed Making Officer and the Association Honorary Council. Comparison of supervision between supervisory institutions is focused on four things, namely the form of supervision, type of supervision, supervisory mechanism and authority & scope of supervision. Based on these four things, the Supervisory Board is the best supervisory agency, while the other three supervisory institutions need to be improved through changes or additions to their legal rules.